IN-VITRO EVALUATION OF PHYSICOCHEMICAL, ANTIOXIDANT AND ANTI-INFLAMMATORY ACTIVITY OF POMEGRANATE (PUNICA GRANATUM L.) JUICE AND SEED HYDRO EXTRACTS - MANUKUMAR H.M,; THRIBHUVAN K.R, (International Journal of Pharma and Bio Sciences, 2014)
This study evaluated, for the physicochemical, antioxidant, and anti-inflammatory activities using vitro assays of water extracts from juice and seed of commercially grown pomegranate fruit. The fruit weight, fruit length, fruit volume, fruit length and fruit diameter, were in the range of 258.33 g, 264.77 cm3, 72.42 mm and 76.03 mm respectively. Total soluble solids content, pH, titratable acidity and total sugars are matching the literature reviewed. Juice having higher total phenolic content and fewer flavonoid contents and visa versa in seed. Antioxidative property was deliberated based on their free radical scavenging ability and reducing power, in which the juice exerted higher (48% and 310µg/ml) potential than seed (36% and 297 µg/ml) respectively. The investigated results against normal erythrocytes exposed to both heat and hypotonic induced lyses exhibited juice (49.23% and 29.65%) have higher potency than seed (36.25% and 19.57%) at 1mg/ml compared to the standard drug acetyl salicylic acid (64.28% and 52.29%) at 0.1mg/ml respectively